Urgency of implementing adab for students of elementary school in the perspective of the Qur’an and hadith - Lilis Sumaryanti; Aldo Redho Syam; Azid Syukroni (AL-ASASIYYA: Journal Of Basic Education, 2020)
Adab is very important in life, be it one's own life, family or social life and what is more important is adab to Allah and His Messenger. Cultivating adab for students of elementary school is an effort taught to students to shape them into true and noble Muslims before Allah, His Messenger, and fellow humans because adab is a barometer of the perfection of faith. The purpose of writing this study is to describe the urgency of implementing adab for students of elementary school from the perspective of the Qur’an and hadith. This research is the result of a literature review with data obtained from document study studies, both from reference books and international and national scientific journals. This study suggests that the Qur’an and hadith have explained a lot about the importance of adab in the daily life of a muslim. The application of adab for students of elementary school, as explained in the Qur’an and hadith is a form of effort that is taught to them to realize insan kamil kaffah and able to carry out the knowledge that has been taught to them perfectly and maintain it completely so that it can be useful in this world and the hereafter.